Domestic vs international risk diversification possibilities in Southeastern European stock markets - Sinisa Bogdan; Suzana Baresa; Zoran Ivanovic (UTMS Journal of Economics, 2016)
Modern portfolio theory is one of the most important investment decision tools in finances. In 1952 Harry Markowitz set the foundations of the Modern portfolio theory, since than this theory was a backbone of many studies that dealt with investment decisions. This research applies mean-variance portfolio optimization on the international Southeastern Europe and domestic Croatian stock market exchange. Aim of this research is to compare risk diversification possibilities on the Southeastern European capital markets and on the Croatian Capital market. By analyzing nine stock market indices in the Southeastern Europe and twenty stocks from Zagreb Stock Exchange in the period of 36 months, results clearly show that internationally diversified portfolios offer better portfolio risk reduction than domestically diversified portfolios. Lowest achieved risk in international portfolio outperformed lowest achieved risk in domestic portfolio. Since risk is lower, returns are also much lower compared to domestic stock portfolios. Results of this research also report that domestic stock portfolios outperformed international portfolios at the risk level equal or higher than 0,97%, for the same risk, domestic portfolios offer greater returns.
Keywords: G11; C61; 330; modern portfolio theory; portfolio optimization; stock portfolio; stock market indices; Zagreb stock exchange